Quality of life 10 years after cardiac surgery in adults: a long-term follow-up study - Vincelj, Josip (Health Qual Life Outcomes, 2020)
We have read the article titled „Quality of life 10 years after cardiac surgery in adults: a long-term follow-up study “ by Perrotti A. et al. published in your distinguished journal with great interest. Unfortunately, we found few errors in this article.